Kicking kinematic profiles during a 50 m butterfly race - Gonjo, T.; Raffalt, P.; Olstad, B. H. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Although evidence indirectly suggests that swimmers likely adjust their movement in a complex manner, no studies have quantified how the frequencies, as well as other related kinematic factors, change throughout the underwater and surface swimming segments during butterfly races. Identifying such behaviours is of great importance for practitioners to consider appropriate training and drills that are directly related to swimming races. Therefore, the purpose of this study was to investigate the lower limb kinematic profile throughout a butterfly swimming race.